A real-time assessment of customer experience - Stein, Alisha Sarah (Curtin University, 2015)
We have now entered into the age of the customer, a time where competing through traditional methods is no longer valid; it is the customer experience that is crucial to gaining a competitive advantage. Despite the recognition of the importance of customer experience, there is a considerable dearth of knowledge among both academics and practitioners on aspects relating to customer experience including the drivers, measurement and value it provides to firms. In an attempt to move forward the body of knowledge on customer experience, the researcher set out to answer the following research question: what is the impact of customer experience on customer intentions and actual behaviour in multichannel retail and service settings? The research comprised two successive studies. Study 1 was conducted to identify the elements that encompass customer experience touch points. The study was based on a qualitative research approach, using a sequential incident technique to guide the data collection. A total of 28 customer experience narratives provided by 22 informants was collected through semi-structured interviews. An inductive thematic analysis of the semi-structure interview transcripts was employed to identify distinct elements of customer experience touch points; elements to be used to develop a holistic model of customer experience in Study 2. Study 2 was conducted to investigate empirically the real-time impact of customer experience on customer intentions and actual behaviour in multichannel retail and service settings.